الهندسة الكسرية في العمارة التقليدية - سعيد, نسيبة; بصيص, محمد; شدود, شذا (Latakia University Journal -Engineering Sciences Series, 2018)
It’s often debated that architecture has a controversial relationship with mathematics on the one hand and with nature on the other. Many scientific theories that deal with and try to explain the natural phenomena have been developed recently. One of these theories is the fractal geometry. It has been used in architecture to study and analyse the environment being built. Trying to find some new solutions inspired by the spirit of the traditional buildings, some studies have attempted to get benefit of their applications in the study of such buildings. However, they have depended on the fractional properties in order to avoid any literal repetition of the traditional aspects, any visual chaos or any distortion of the old cities. The fractional geometry and its existence in the traditional buildings facades have been discussed by a research that shows its definition in addition to its most important characteristics. A sample of the traditional buildings was then analyzed using a program called fractalyse. This program is based on fractal geometry to calculate the sample first. Then to compare and analyse the results until reaching the conclusion that the traditional architecture has a fractal structure. This structure helps to adopt the characteristics of this sample as reference when designing the neighboring building facades. تبرز من حين لآخر جدلية العلاقة بين العمارة والرياضيات من جهة، وبين العمارة والطبيعة من جهة أخرى، وخلال الاعوام الماضية ظهرت العديد من النظريات العلمية الحديثة التي تعنى بالظواهر الطبيعية وتحاول تفسيرها، ومن هذه النظريات الهندسة الكسرية التي بدأت تستخدم في العمارة لدراسة البيئة المبنية وتحليها، وظهرت بعض الدراسات التي حاولت الاستفادة من تطبيقاتها في دراسة المباني التقليدية لإيجاد حلول جديدة مستوحاة من روحها ولكن دون التكرار الحرفي لمفرداتها، وذلك من خلال الاستفادة من الخصائص الكسرية الموجودة في المباني التقليدية، ومحاولة تكرارها باستخدام مواد ومفردات حديثة، بحيث تقلل من الفوضى البصرية وتحد من طمس معالم المدن القديمة وتشويهها. يناقش البحث الهندسة الكسرية ومدى وجودها في واجهات المباني التقليدية، من خلال استعراض تعريفها وأهم خصائصها، ومن ثم تم تحديد عينة بحثية من المباني التقليدية، وتحليلها باستخدام برنامج Fractalyse الذي يعتمد على الكسرية، لحساب البعد الكسري للعينة ومقارنة النتائج وتحليلها وصولا الى الاستنتاجات بان العمارة التقليدية تتمتع ببنية كسرية بهدف اعتماد خصائص هذه البنية كمرجع في عملية تصميم واجهات المباني الحديثة المجاورة لها بالاستناد عليها.